Magnitude of Potentially Inappropriate Thrombophilia Testing in the Inpatient Hospital Setting. Issue 9 (1st September 2017) - Mou, Eric; Kwang, Henry; Hom, Jason; Shieh, Lisa; Kumar, Andre; Richman, Ilana; Berube, Caroline
Abstract : Laboratory costs of thrombophilia testing exceed an estimated 650 million (in US dollars) annually. Quantifying the prevalence and financial impact of potentially inappropriate testing in the inpatient hospital setting represents an integral component of the effort to reduce healthcare expenditures. We conducted a retrospective analysis of our electronic medical record to evaluate 2 years' worth of inpatient thrombophilia testing measured against preformulated appropriateness criteria. Cost data were obtained from the Centers for Medicare and Medicaid Services 2016 Clinical Laboratory Fee Schedule. Of the 1817 orders analyzed, 777 (42.7%) were potentially inappropriate, with an associated cost of 40, 422. The tests most frequently inappropriately ordered were Factor V Leiden, prothrombin gene mutation, protein C and S activity levels, antithrombin activity levels, and the lupus anticoagulant. Potentially inappropriate thrombophilia testing is common and costly. These data demonstrate a need for institution‐wide changes in order to reduce unnecessary expenditures and improve patient care.